A Door Lock Security System with Remote Keyless Feature Using The Puf Approach Method - Ramadhan, Muhamad Noveri; Yendri, Dodon (Universitas Andalas, 2025)
Home security systems are now increasingly important to provide peace and comfort, Especially if the occupants often leave the house. As the main access point, the door is an important thing to pay attention to in maintaining home security. Smart door locks offer better security features compared to traditional mechanical lock. However, technology that relies on smartphones or PINs has vulnerability to attacks such as brute force and various digital security threats. Besides that, The limitations of human memory pose challenges in maintaining security. This research develops a door security system with remote keyless feature using the Physical Unclonable Function (PUF) approach and Bluetooth connectivity as a communication system. The system uses RSSI values to provide remote control and reminders, ensuring automatic locking at a certain distance. Test results show that this system effectively providing unique security and convenience for users. The use of servo motor ensures precision in locking, while the ESP32 is used for communication and generates a unique PUF values, making the system more secure and resistant to duplication.